2013
DOI: 10.1177/1060028013514031
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Exclusivity

Abstract: Amendments to FDAAA are needed to ensure that studies approved for exclusivity strive to meet the following requirements: relevant pediatric clinical indication ; disease addressed should represent a significant disease burden to the appropriate population; important age ranges should be covered; studies should not be allowed when a safety signal is identified prior to initiation of the study; and trials where endpoints are successfully achieved providing considerable contribution to pediatric dosing knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…21 One study 22 found that, of nearly 200 drugs studied in pediatric populations between 1998 and 2012, 57% resulted in new or expanded pediatric indications for the drugs being studied, although the clinical utility of some of the trials conducted to earn the extension has been criticized. 23 Pediatric exclusivity, however, is a very costly means of ensuring that the needed clinical research in children is performed. An analysis found that the revenues collected because of the additional monopoly protection granted to manufacturers from pediatric exclusivity far exceeded their cost for performing these trials; the net economic benefit was $134 million per drug (range, −$9 million to $508 million), a profit ratio of more than 10 to 1.…”
Section: Pediatric Exclusivitymentioning
confidence: 99%
See 1 more Smart Citation
“…21 One study 22 found that, of nearly 200 drugs studied in pediatric populations between 1998 and 2012, 57% resulted in new or expanded pediatric indications for the drugs being studied, although the clinical utility of some of the trials conducted to earn the extension has been criticized. 23 Pediatric exclusivity, however, is a very costly means of ensuring that the needed clinical research in children is performed. An analysis found that the revenues collected because of the additional monopoly protection granted to manufacturers from pediatric exclusivity far exceeded their cost for performing these trials; the net economic benefit was $134 million per drug (range, −$9 million to $508 million), a profit ratio of more than 10 to 1.…”
Section: Pediatric Exclusivitymentioning
confidence: 99%
“…Hundreds of drugs have been granted pediatric exclusivity since the program was created . One study found that, of nearly 200 drugs studied in pediatric populations between 1998 and 2012, 57% resulted in new or expanded pediatric indications for the drugs being studied, although the clinical utility of some of the trials conducted to earn the extension has been criticized …”
Section: Patent Exclusivitymentioning
confidence: 99%
“…Pediatric drug development should be driven by the identified pediatric needs and must consider applicable regulatory requirements and recommendations [2]. With the implementation of several pediatric policies in both Europe and the USA, and the strong support of various advocacy groups and of the pediatric community, pediatric research has made significant progress [3,4] over the last decade. To make safe and effective medicines available for the pediatric population, timely development of evidence on the proper use of products in pediatric patients of various ages is needed, taking into account not only regulatory guidelines [2] and clinical recommendations, but also specific tools, trial designs, and methods [5], including the pharmaceutical design of pediatric formulations [6].…”
Section: Why Is There a Need For A Specific Pediatric Structure?mentioning
confidence: 99%
“…The pediatric exclusivity program was enacted as a 5-year pilot as part of the FDA Modernization Act of 1997 . It was then integrated into the Best Pharmaceuticals for Children Act (BPCA) in 2002, renewed in 2007, and made permanent in 2012 . Separately, the Pediatric Research Equity Act of 2003 (PREA) requires pediatric studies for approved indications of drugs without a market exclusivity extension when the FDA identifies a need to improve pediatric labeling .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] It was then integrated into the Best Pharmaceuticals for Children Act (BPCA) in 2002, renewed in 2007, and made permanent in 2012. 6,7 Separately, the Pediatric Research Equity Act of 2003 (PREA) requires pediatric studies for approved indications of drugs without a market exclusivity extension when the FDA identifies a need to improve pediatric labeling. 8,9 For drugs subject to a PREA mandate, sponsors may propose that 1 or more of its mandated trials form the basis of a formal Written Request for pediatric studies that, if approved, provides pediatric exclusivity extensions under BPCA for completion of PREA-mandated trials.…”
mentioning
confidence: 99%